Cross-Lagged Relationships between Morphological Awareness and Reading Comprehension among Chinese Children - Cheng, Yahua; Zhang, Jie; Wu, Xinchun; Liu, Hongyun; Li, Hong (Frontiers in Psychology, 2016)
The present study examined the developmental relationship between morphological awareness and reading comprehension using a two-year and four-wave cross-lagged design with a sample of 149 Chinese children (80 male and 69 female). We measured children’s morphological awareness, word reading, and reading comprehension from T1 to T4, in addition to phonological awareness, vocabulary knowledge, and general cognitive ability at T1 as control measures. Four plausible cross-lagged models were assessed and compared to examine the direction of the developmental relationships between morphological awareness and reading comprehension over time. Results found support for a reciprocal-causation model, that is, morphological awareness stably predicted subsequent reading comprehension, and the reverse relation was also found. Longitudinal mediation analyses revealed that word reading partially mediated the relationship between morphological awareness and reading comprehension in Chinese children. These findings extend our understanding of the relationship between morphological awareness and reading comprehension. The practical implications for these two developing skills in Chinese children are discussed.